(untitled) (CIPEEX, 2025)
The elderly population frequently faces a decrease in calorie and protein intake, a phenomenon that plays a fundamental role in the sharp loss of muscle mass and strength. This nutritional decline is directly associated with the weakening of muscle reserves, which can manifest in various adverse health consequences. The reduction in the intake of essential nutrients compromises not only the structural integrity of the muscles but also their functional capacity (CHEN et al, 2022). The effects of this muscle loss are comprehensive and affect various dimensions of physical and respiratory function. The decrease in muscle mass has direct implications on respiratory and peripheral strength, significantly affecting the efficiency with which the body performs vital functions. This deterioration in strength and functional capacity can lead to a generalized impairment of pulmonary function, highlighting the importance of maintaining adequate nutrition to preserve the health and well-being of the elderly (CHEN et al, 2022). In addition to the physical impacts, the reduction in muscle mass and the consequent loss of strength can have far-reaching repercussions on the quality of life of elderly individuals. The reduced capacity to perform daily activities and the increased vulnerability to respiratory diseases underscore the urgent need for targeted nutritional strategies and public health interventions to mitigate the adverse effects of malnutrition in this age group (AHMED AND HABOUBI, 2010). Therefore, the objective of this study was to evaluate the effects of isolated whey protein supplementation over 12 weeks on pulmonary function, respiratory and peripheral muscle strength, and functional capacity.